Search for CP violation in the decay D±→K0Sπ± - Amo Sanchez, Pablo del; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We report on a search for CP violation in the decay D±→K0Sπ± using a data set corresponding to an integrated luminosity of 469 fb−1 collected with the BABAR detector at the PEP-II asymmetric energy e+e− storage rings. The CP-violating decay rate asymmetry ACP is determined to be (−0.44±0.13(stat)±0.10(syst))%, consistent with zero at 2.7σ and with the standard model prediction of (−0.332±0.006)%. This is currently the most precise measurement of this parameter.
*BABAR Collaboration: P. del Amo Sanchez, J. Marks, U. Uwer [und 429 weitere Personen]
Im Titel ist das Plus- und Minuszeichen hochgestellt
Im Titel ist die Zahl 0 hochgestellt
Im Titel ist der Buchstabe S tiefgestellt
Gesehen am 05.10.2022